Wild Objectification: Social Work as Object - Nissen, Morten (Outlines. Critical Practice Studies, 2004)
The paper is about objectification in and of social work. Drawing on a decade-long cooperation with a Copenhagen social workers network focused in the organization Wild Learning, and starting from an Internet essay this organization has provided, the problems with objectifying social work are discussed. Viewed as basically a wholistic subjectification, social work cannot easily be endowed with objectivity in the form of scientific standards, and the objects representing it are often like novels, uniqueness mass-produced; they can be said to ideologically confirm rather than scientifically model its activities and communities. The approach to objectification must dig a level deeper. It is considered how objectifications in social work – and the Internet essay is taken as example – can be approached critically as ideological objectifications and at the same time, in the cultural-historical tradition, as prototypes with some scope of relevance.